2013
DOI: 10.1038/ncomms2404
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic RNA devices to expedite the evolution of metabolite-producing microbes

Abstract: An extension of directed evolution strategies to genome-wide variations increases the chance of obtaining metabolite-overproducing microbes. However, a general high-throughput screening platform for selecting improved strains remains out of reach. Here, to expedite the evolution of metabolite-producing microbes, we utilize synthetic RNA devices comprising a riboswitch and a selection module that specifically sense inconspicuous metabolites. Using L-lysine-producing Escherichia coli as a model system, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
124
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 45 publications
1
124
0
2
Order By: Relevance
“…Biosensors that report on the concentration of a chemical within each individual cell can alleviate this screening bottleneck (10). Such sensor reporters transduce the binding of a target small molecule by a sensory protein or RNA into a gene expression readout (7).…”
mentioning
confidence: 99%
“…Biosensors that report on the concentration of a chemical within each individual cell can alleviate this screening bottleneck (10). Such sensor reporters transduce the binding of a target small molecule by a sensory protein or RNA into a gene expression readout (7).…”
mentioning
confidence: 99%
“…Engineers have begun developing strategies for multiplexed evaluation of metabolite production phenotypes to enable a fully multiplexed design-build-test cycle (1,(4)(5)(6)(7). In cases of genetic engineering, such a design cycle would more closely resemble biological evolution, rather than the design approaches inspired by electrical engineering that currently dominate the fields of synthetic biology and metabolic engineering.…”
mentioning
confidence: 99%
“…Structural analysis of the Llysine binding aptamer domain of this RNA revealed that it completely encapsulates the ligand and therefore must undergo a structural opening/closing procedure to regulate the enzyme activity upon interaction with Llysine (Muranaka et al 2009;Yang et al 2013). A genetic RNA device comprising the L-lysine riboswitch could be used to monitor the alteration of phenotypes caused by changes in the intracellular concentration of L-lysine and to facilitate the strain improvement (Yang et al 2013). However, this device has not been used in screening the evolved aspartate kinase.…”
Section: Introductionmentioning
confidence: 98%
“…As a majority of target products are not associated with a conspicuous phenotype of the host, the desired property cannot be readily obtained without a general screening tool with the ability of detecting the target products and capacity for high-throughput screening (Dietrich et al 2010;Yang et al 2013). Recent studies demonstrated that natural RNA molecules, such as riboswitch, can recognize small organic compounds, harness allosteric changes, and control the expression of adjacent genes at the levels of transcription, translation, and RNA degradation (Mironov et al 2002;Nahvi et al 2002;Winkler et al 2002).…”
Section: Introductionmentioning
confidence: 99%